2019
DOI: 10.1111/plb.12990
|View full text |Cite
|
Sign up to set email alerts
|

Calcium acetate‐induced reduction of cadmium accumulation in Oryza sativa: Expression of auto‐inhibited calcium‐ATPase and cadmium transporters

Abstract: Calcium (Ca) signalling has an essential role in regulating plant responses to various abiotic stresses.• This study applied Ca in various forms (Ca acetate and CaCl 2 ) and concentrations to reduce cadmium (Cd) concentration in rice and propose a possible mechanism through which Ca acts to control the Cd concentration in rice.• The results showed that supplementation of Cd-contaminated soil with Ca acetate reduced the Cd concentration in rice after exposure for 7 days in both hydroponic and soil conditions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Increasing the external Ca concentration significantly downregulated the expression of OsNRAMP1 and OsNRAMP5 (Figure 3A,B). Likewise, Treesubsuntorn and Thiravetyan [47] also reported a downregulation of OsNRAMP5 in rice plants upon applying calcium acetate (Ca(CH 3 COO) 2 ) in soil. These results proved that Ca could also decrease Cd uptake into rice roots by suppressing the expression of OsNRAMP1 and OsNRAMP5.…”
Section: Ca Decreases Root CD Uptake In Rice Not Only By Competing For Absorption Sites But Also By Suppressing the Expression Of Osnrampmentioning
confidence: 93%
See 2 more Smart Citations
“…Increasing the external Ca concentration significantly downregulated the expression of OsNRAMP1 and OsNRAMP5 (Figure 3A,B). Likewise, Treesubsuntorn and Thiravetyan [47] also reported a downregulation of OsNRAMP5 in rice plants upon applying calcium acetate (Ca(CH 3 COO) 2 ) in soil. These results proved that Ca could also decrease Cd uptake into rice roots by suppressing the expression of OsNRAMP1 and OsNRAMP5.…”
Section: Ca Decreases Root CD Uptake In Rice Not Only By Competing For Absorption Sites But Also By Suppressing the Expression Of Osnrampmentioning
confidence: 93%
“…Apart from Cd uptake in the roots, the translocation of Cd from roots to shoots is another critical process controlling the accumulation of Cd in the aboveground tissues of rice plants [1,49]. It has been reported that Ca treatment reduced Cd accumulation in the aboveground parts of rice and Gamblea innovans [47,50]. On the contrary, many other studies revealed that Ca could also induce Cd translocation from roots to shoots in Arabidopsis [51], chamomile [52], and rice [33].…”
Section: Ca Facilitates Root-to-shoot CD Translocation In Rice By Modulating the Expression Of Oshmasmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also worth noting that while the rice genome is three times larger than that of Arabidopsis, rice had only one sequence (LOC_Os04g516110) with high identity with AtACA8 (72%), AtACA9 (70%), and AtACA10 (70%), suggesting a common ancestry of these proteins in these two species. However, due to their duplication history, it can be also inferred that rice has other types II Ca 2+ -ATPases with less identity to Arabidopsis (Treesubsuntorn and Thiravetyan, 2019).…”
Section: Evolution Of Acas and Ecasmentioning
confidence: 99%
“…Numerous studies have shown that an increase in cytosolic calcium concentration is one of earliest mechanisms by which plant cells respond to various abiotic stresses such as drought, salt, heat, cold, heavy metal stress, and ozone stress (Evans, McAinsh, Hetherington, & Knight, 2005; Knight, 1999; Li et al, 2016; Niu & Liao, 2016; Reich, Aghajanzadeh, Parmar, Hawkesford, & De Kok, 2018; White & Broadley, 2003). Interestingly, exogenous calcium applications have been reported to ameliorate the adverse effect of stresses on plants in many publications in the last decade (Ahmad et al, 2018; Cha‐um, Singh, Samphumphuang, & Kirdmanee, 2012; Erinle et al, 2016; Naeem et al, 2018; Rahman, Mostofa, Nahar, Hasanuzzaman, & Fujita, 2016; Treesubsuntorn & Thiravetyan, 2019). However, although there are several methods for introducing calcium into plants, there has been nothing reported about foliar spraying calcium directly onto rice leaves under high ozone condition (100 ± 50 ppb).…”
Section: Introductionmentioning
confidence: 99%